Analisis Ratio Decidendi Hakim dalam Kasus Tindak Pidana Penggelapan dalam Jabatan di Pengadilan Indonesia - Ginting, Jan Efraim Hartonta; Wirogioto, Ali Johardi; Saefullah Saefullah (Pusat Riset dan Inovasi Nasional, 2025)
One form of crime that is highly relevant in the context of today's society is the crime of embezzlement in office. This embezzlement can be defined as a dishonest act committed by one or more individuals by hiding goods or property belonging to another person without the owner's knowledge. This action aims to transfer ownership of the goods, which can be categorized as theft, taking possession of goods, or using the goods for unauthorized personal gain. In many cases, embezzlement in office often involves individuals who have access or authority over company assets, making it easier for them to commit misuse. This study applies a normative juridical research method to analyze existing problems in the context of criminal law. This method allows researchers to explore and understand applicable legal norms and how they are applied in real cases. The results of the study show that the Judge's Ratio Decidendi in imposing sanctions on cases of embezzlement in office, as stated in Decision Number 542/Pid.B/2023/PN Cbi and Decision Number 355/Pid.B/2024/PN Cbi, is based on a number of in-depth legal considerations. In this case, the judge first explained the elements contained in Article 374 of the Criminal Code (KUHP) charged by the public prosecutor. The defendant was found guilty of committing embezzlement in office by embezzling company funds for personal gain. Therefore, the defendant was sentenced commensurate with his actions, which violated Article 374 of the Criminal Code. Criminal liability for the perpetrator of the crime of embezzlement in office has been legally and convincingly proven, with all elements of the charge having been fulfilled. This indicates that the perpetrator can be subject to sanctions in accordance with applicable legal provisions, thus providing a deterrent effect and upholding justice in the criminal law system. This research is expected to contribute to the development of understanding regarding embezzlement in office and its legal implications in Indonesia, as well as encourage more effective law enforcement in handling similar cases in the future.